Occupational Stress and Nursing Performance in In-Patient Care: Organizational Determinants in a Nigerian Tertiary Hospital - Abiodun FATUKASI (The Nursing Scope, 2026)
Background: Occupational stress remains a major challenge in nursing practice, particularly in inpatient care settings characterized by demanding workloads, complex clinical responsibilities, and resource constraints. Persistent workplace stress can adversely affect nurses’ performance, clinical decision-making, communication, and patient safety. Despite growing concerns about occupational stress among nurses, evidence regarding its organizational determinants and impact on nursing performance in Nigerian tertiary healthcare institutions remains limited. Aim: This study examined the relationship between occupational stress and nursing performance among nurses working in inpatient care units at Kwara State University Teaching Hospital (KWASUTH), Ilorin, Nigeria, with emphasis on organizational determinants and implications for patient safety. Method: A descriptive cross-sectional survey design was adopted. A total of 113 registered nurses were selected through simple random sampling from inpatient care units at Kwara State University Teaching Hospital (KWASUTH), Ilorin. Data were collected using a structured self-administered questionnaire and analyzed using descriptive and inferential statistics. Chi-square analysis was used to determine the relationship between occupational stress and nursing performance, with statistical significance set at p < .05. Findings: The findings revealed a moderate-to-high level of occupational stress among nurses (Mean = 3.42). Occupational stress negatively influenced nursing performance (Mean = 3.20), particularly in concentration, task efficiency, and emergency decision-making. Organizational stressors had a greater influence on nursing performance (Mean = 3.84) than individual stressors (Mean = 3.67), with inadequate staffing, irregular shift schedules, and excessive workload identified as the principal contributors. A statistically significant relationship was found between occupational stress and nursing performance (χ² = 26.45, p < .05). Conclusion: Occupational stress remains a significant occupational health challenge that adversely affects nursing performance and may compromise patient safety in tertiary healthcare settings. Addressing organizational sources of stress is essential for improving nurses’ performance and enhancing the quality and safety of patient care. Recommendation: Hospital administrators and policymakers should implement evidence-based interventions, including adequate staffing, equitable shift scheduling, workload management, and workplace support programmes, to reduce occupational stress and improve nursing performance and patient outcomes. Keywords: Occupational stress, Nursing performance, Inpatient care, Organizational stressors, Workload